UAV Technology Seminar for Elementary School Teachers - Rafie Djajasoepena; Patrick Lingga; Iwan Setiawan; Kushendarsyah Saptaji; Djati Wibowo; Aditiya Harjon; Ahmad Fadhil Tsani; Eko Sulistyo; Wandy Wandy (Journal of Community Services: Sustainability and Empowerment, 2026)
An Unmanned Aerial Vehicle (UAV) is commonly referred to as a drone or an aircraft with no onboard pilot. The drone technologies have been applied in many sectors such as military, hidden area exploration, medical, and many more. Purpose of this community service activities were to have elementary school teachers have basic knowledge of UAV. Initial discussions established with the teacher a month prior the seminar. Internal discussion more within the faculty members during office days and office hours through weekly offline meeting or via instant messaging service. There were 2 UAVs prepared for this seminar, and the school also already have drone for event documentation operational purposes. D-day seminar activities were only 2 hours on 27 November 2025 including preparation in the school classroom. Post-seminar activities were generating certificates for the resource persons also for all participants. The seminar has been successfully conducted with around 10 participants. Participants earned the basic knowledge about UAVs delivered by the resource person; this was essential to have both technical and non-technical information about the UAVs for teachers.